DETERMINATION OF GROUNDWATER CONSERVATION ZONE BASED ON SIMULATION OF DECREASING GROUNDWATER TABLE AT UNCONFINED AQUIFER IN BANJARBARU CITY - Sahbani, Ilman
Banjarbaru City officially became the capital city of South Kalimantan Province replacing Banjarmasin City after the ratification of RI Law Number 8 of 2022 Urban development causes groundwater use to increase and groundwater recharge capacity to decrease due to land conversion to built-up land. Simulating groundwater subsidence using the MODFLOW through the QGIS-FREEWAT program with several scenario models by intervening in pumping of groundwater discharge and groundwater recharge values. The level of damage to the lowering of the groundwater level, as well as the determination of groundwater conservation zones refers to Permen of ESDM Number 31 of 2018 which consists of groundwater protection zones and groundwater utilization zones. The groundwater conservation zone simulation of Banjarbaru City for the groundwater protection zone covers a main recharge area of 4.18 km2 and a protected forest area of 13.07 km2 and for the groundwater utilization zone includes a safe zone of 130 km2, a vulnerable zone of 42 km2, a sub zone critical area of 19 km2, and sub-damaged zone of 91 km2. In the critical to vulnerable sub-zones, it is necessary to re-plan groundwater use, limit it, prioritize groundwater and seek alternatives for clean water supply and create artificial recharge.